Insights on the Nutraceutical Properties of Different Specialty Teas Grown and Processed in a German Tea Garden - Patricia Carloni; Federico Girolametti; Elisabetta Giorgini; Tiziana Bacchetti; Cristina Truzzi; Silvia Illuminati; Elisabetta Damiani (MDPI AG, 2023)
European countries have recently started experimenting with growing and producing their own teas in small quantities, mainly for the specialty tea sector. To characterize European teas, this study investigated a set of five tea types obtained from different Camellia sinensis varieties/cultivars, representing various oxidation grades (green, white, yellow, oolong, black), all grown and processed in the only tea garden in Europe (in Germany) that focuses on all five types. Hot and cold brews were studied by measuring the total phenolic (TPC) and flavonoid contents (TFC), the antioxidant capacity and UV-Vis spectra, also with the objective of discriminating between the different tea types and the different plant varieties. The dried leaves were analyzed to measure the content of essential and toxic elements and by ATR-FTIR spectroscopy to determine a chemical fingerprint for identifying the tea varieties and types. The average levels of TPC (hot brew = 5.82 ± 2.06; cold brew = 5.4 ± 2.46 mM GAEq), TFC (hot brew = 0.87 ± 0.309; cold brew = 0.87 ± 0.413 mM CAEq), and antioxidant capacity (ORAC assay-hot brew = 20.9 ± 605; cold brew = 21.8 ± 8.0 mM TXEq, ABTS assay-hot brew = 15.2 ± 5.09; cold brew = 15.1 ± 5.8 mM TXEq, FRAP assay-hot brew = 9.2 ± 3.84; cold brew = 10.4 ± 5.23 mM AAEq) observed compared well with those from other parts of the world such as China, Africa, and Taiwan. The hazard quotient <1 and the hazard index of 0.14 indicate that there is no non-carcinogenic risk from consumption of these teas. The obtained information is essential for elucidating the characteristics and the impact of tea processing and tea variety on the health benefits of these tea products coming from a single European tea garden. This multifaceted approach would help tea growers in Europe increase their knowledge on the health attributes of the teas they grow, ultimately leading to optimization of the nutraceutical properties of these teas.